A rare case of IgG4-related aortitis in the thoracic aorta mimicking an intramural hematoma: navigating the diagnostic labyrinth - Victor S. Alemany; Jacqueline Fortier; Himanshu Gupta; Arik Zaider; Juan Grau; Paul Burns; Habib Jabagi (Journal of Cardiothoracic Surgery, 2024)
Abstract A 54-year-old female presented with recurrent abdominal pain and new onset chest pain. Chest computed-tomography angiogram detected a thoracic aortic aneurysm with suspected Type A intramural hematoma (IMH) versus aortitis. Initially, conservative management was pursued while awaiting a definitive diagnosis. Differential workup was negative, while additional imaging modalities favored IMH, prompting expedited surgical intervention. During ascending aortic and hemiarch replacement, severe aortitis was unexpectedly discovered without evidence of IMH. Histopathological examination of the aortic specimens identified transmural aortic inflammation with lymphoplasmacytic infiltrate and irregular fibrosis. Numerous IgG4-positive plasma cells were present with IgG4/IgG ratio of 40–50% suggesting IgG4-related disease (IgG4-RD). Subsequent analysis revealed B cells positive for clonal IgH gene rearrangement, and bone marrow biopsy then revealed the same clonal B cells. She was ultimately diagnosed with CLL, the most common phenotype of monoclonal B-cell lymphocytosis, thought to account for the IgG4-predominant plasma cells causing aortitis. Although rare, this case highlights the importance of considering IgG4-related disease (IgG4-RD) as a cause of aortitis when assessing symptomatic patients with aortic pathologies, emphasizing the complexities involved in diagnosing due to a variety of imaging presentation, differentiating, and managing large-vessel vasculitides. Moreover, it underscores the importance of Multidisciplinary Aortic Team care and the use of multiple diagnostic modalities in evaluating ambiguous aortic pathologies.